Localized congenital hypertrichosis/Hairy nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2013)
Localized congenital hypertrichosis (LCH) is characterized by an area (on the midline) or two areas (bilateral and symmetrical) of terminal hairs without any other alteration of the underlying skin. Proper hairy nevus (HN) is characterized by an area of skin distributed over a single segment, not on the midline, with terminal hairs without any other alteration of the underlying skin. Both lesions are present from the earliest stages of life and persist throughout life. Despite these similarities, localized hypertrichosis of the midline is associated more frequently with other malformations and therefore has a different prognostic significance.